2011
DOI: 10.1057/hsq.2011.2
|View full text |Cite
|
Sign up to set email alerts
|

Deriving trends in life expectancy by the National Statistics Socio‐economic Classification using the ONS Longitudinal Study

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 8 publications
(10 reference statements)
1
11
0
Order By: Relevance
“…For example, it is known that mortality rates differ between manual and non-manual workers (Johnson 2011), between different geographical regions (Office for National Statistics 2011), and between birth cohorts (Willetts 2004). There has been concern that companies' mortality assumptions may not be up-to-date, failing to reflect increases in life expectancy (Pensions Regulator 2006;Club Vita 2011).…”
Section: Regulatory Backgroundmentioning
confidence: 99%
“…For example, it is known that mortality rates differ between manual and non-manual workers (Johnson 2011), between different geographical regions (Office for National Statistics 2011), and between birth cohorts (Willetts 2004). There has been concern that companies' mortality assumptions may not be up-to-date, failing to reflect increases in life expectancy (Pensions Regulator 2006;Club Vita 2011).…”
Section: Regulatory Backgroundmentioning
confidence: 99%
“…In particular, there is a well established inverse relationship between socio-economic circumstances -whether measured by educational attainment, occupation, income or area deprivation -and mortality, with higher socio-economic subgroups having lower mortality rates and, in most cases, also experiencing faster mortality improvements than lower socioeconomic subgroups (see, e.g., Shkolnikov et al (2006); Johnson (2011);Tarkiainen et al (2012); Raleigh and Kiri (1997)). …”
Section: Introductionmentioning
confidence: 99%
“…This increase in deaths, particularly in the upper age groups of the range, remains unexplained. A general comparison with longer-term trends in female life expectancy, (Johnson, 2011) suggested that the pattern for the most advantaged classes (Higher managers and professionals and Lower managers and professionals) was reflected in the results of the current study, with these classes experiencing the greatest growth in life expectancy over twenty years and the greatest decline in mortality between 2001 and 2006. However, there is no indication in the life expectancy estimates to suggest a poor trend performance in mortality rate for Semi-routine occupations, nor is there evidence of a greater than average recent improvement in the mortality of the Routine class, as suggested by the results from the current study.…”
Section: Discussionmentioning
confidence: 51%